Postulat uporządkowania prawa w Anonima “De rebus bellicis” - Wiewiorowski, Jacek (Studia Europaea Gnesnensia, 2012)
Text discusses the Anonymus de rebus bellicis (DRB) - written in late 4th or early 5th century - proposals concerning the necessity to reform the ambiguity of law (DRB XXI). Author gathers opinions of modern scholars about the value, limits and influence of DRB XXI in the matter of so called codification of Roman law in Late Antiquity, adding to it his own interpretation of its text (with first Polish translation of the fragment by dr Anna Kotłowska, IH AMU Poznań). He deduces that DRB was the isolated petition of private citizen, and his ideas concerning the reform of leges and iura had no ties with project of Theodosian Code or other initiatives to order Roman law in the period. Author concludes that the main value of DRB XXI is the idea of improvement of law by emperor as a way to make better the internal state affairs, what was unfamiliar to contemporaries before writing of this treatise.